FRI.ART : made in Switzerland. - The Clocktower, New York; Franklin Furnace, New York (Fribourg : FRI-ART Centre d'Art Contemporain - Kunsthalle, 1985)
Armleder, John ; Oppenheim, Meret ; Defraoui, Cherif + Silvie ; Müller, Felix ; Müller, Grégoire ; Otth, Jean ; Raetz, Markus ; Walker, Aldo ; Roth, Dieter ; Anüll, Ian ; Berset, Daniel ; Container TV ; Deléglise, Philippe ; Descioux, Etienne ; Egli, Jürg ; Ferrand, Pierre André ; Gilgen, Hans Jürg ; Himmelsbach, Rut ; Ingold, Res ; Ritter, Michel ; Schill, Ruedi ; Signer, Roman ; Trachsel, Peter ; Remond, Knut ; Winteler, Anna ; etc.
FRI.ART made in Switzerland, New York: April 26 - June 8, 1985 : The Clocktower, New York, April 26 - June 2 ; Franklin Furnace, New York, April 26 - June 8 ; The Kitchen, April 30 - May 11 + LA MAMA E.T.C., New York, May 1 - 4 ; The Collective for Living Cinema, New York, May 10, 11, 12
boek
Keywords: Zwitserland